Crystal structure, Hirshfeld surface analysis, DFT and molecular docking studies of 4′-(benzyloxy)-[1,1′-biphenyl]-3-carboxylic acid - M. Harish Kumar; M. Vinduvahini; H. T. Srinivasa; H. C. Devarajegowda; B. S. Palakshamurthy (Acta Crystallographica Section E: Crystallographic Communications)
In the title compound, C20H16O3, intramolecular C— H...O hydrogen bonds are observed. The dihedral angles between the aromatic benzoic acid ring and the two adjacent aromatic rings are 26.09 (4) and 69.93 (8)°, while the dihedral angle between the aromatic rings connected by the C—O—C—C [torsion angle = −175.9 (2)°] link is 89.11 (3)°. In the crystal, inversion dimers linked by pairs of O—H...O hydrogen bonds generate R22(8) ring motifs. These dimers are further linked by C—H...π interactions, forming molecular sheets along (010). The molecular structure was optimized by density functional theory (DFT) at the B3LYP/6–311+ G(d,p) level and the bond lengths, angles and torsion angles were compared with experimental values obtained by X-ray diffraction. The HOMO and LUMO were calculated, the energy gap between them being 4.3337 eV. Further, the intermolecular interactions were quantified using Hirshfeld surface analysis and fingerprint plots and energy frameworks were generated. The two-dimensional fingerprint plots indicate that the major contributions to the crystal packing are from H...H (39.7%), H...C (39.0%) and H...O (18.0%) interactions. The energy framework calculations reveal that the dispersion energy (Edis= 201.0 kJ mol−1) dominates the other energies. Molecular docking studies were carried out for the title compound as a ligand and the SARS-Covid-2 (PDB ID:8BEC) protein, specifically the Omicron variant, was used as a receptor giving a binding affinity of −7.6 kcal mol−1.